Changing the emergency response culture: case of Korea. Issue 1 (29th November 2017) - Ha, Kyoo-Man
Abstract : Purpose: Culture does matter in the field of emergency response. The purpose of this paper is to examine how to change the negative emergency response culture in Korea by relying on people's awareness and the president's leadership. Design/methodology/approach: Qualitative content analysis is used as the methodology. The irresponsibility culture, including public officials' ranking, factionalism, lack of emergency response principles, and social corruption, is contrasted with the responsibility culture, including ability of public officials, egalitarianism, use of emergency response principles, and cleanup of corruption. Findings: The major tenet is that Korea must not miss the opportunity to change its current irresponsibility culture into a responsibility culture under its own environment. Originality/value: Many researchers have raised the necessity of cultural change in the emergency response in Korea during these days. In this regard, this paper studies the Korean emergency response culture more rigorously than did previous studies.